Farmers’ acceptability of hybrid rice in Brgy. Ruparan, Digos City - Jimenez, Lester John; Entero, Ojela Mae; Te, Johnicar Jr.; Carballo, Joy (UM Digos Research Journal, 2016)
The study determines the socio-demographic, farming characteristics, and farming inputs of hybrid rice technology farmers in Ruparan, Digos City, as well as the willingness-to-accept of farmers and the substantial dynamics that significantly influenced farmer's hybrid rice technology. The use of the nonexperimental descriptive-causative method is distinguished and the factors that may link to the livelihood of adopting hybrid rice technology. The gathered data were taken from 50 respondents/farmers through a household survey. The Probit model was utilized to determine which of the farmers' socio-demographic willingness to adopt hybrid rice technology. Results revealed that, on average, hybrid rice farmers are 48.05years old, mostly females, and are prominently married, with educational attainment of 9.45 years and a household size of 4.13. The harmers who intend to adopt hybrid rice technology have a farm size of 5.65 hectares. The seeds of the farmers who intend to adopt the average expenses are Php 4,627.90 per hectare. The average expenses for fertilizer of the farmers who intend to adopt have an average expense of Php 17,684.00 per hectare while employing at least seven helpers on the farm. Probit analysis revealed that age and access to credit were significant factors that determine willingness to accept hybrid rice technology.